2011
DOI: 10.2485/jhtb.20.217
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Low-Intensity Pulsed Ultrasound in a Rat Calvarial Guided Bone-Regeneration Model

Abstract: Abstract:Low-intensity pulsed ultrasound (LIPUS) is a biophysical intervention used to repair bone. LIPUS may reduce the healing time of bone defects covered with osteoconductive membranes. The purpose of this study was to identify the required characteristics of membranes used with LIPUS in guided bone-regeneration (GBR) procedures. Two bioabsorbable membranes (Bio-Mend ® , GC membrane), one non-bioabsorbable membrane (GORE-TEX ® ), and one titanium membrane (FRIOS ® BoneShield) were evaluated with an oscillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Figures 1 and 2 show the evolution of bone growth around the defect as observed during a period of approximately 1 month for the control group (not treated with ultrasound) and for the group treated with LIPUS. From the results observed by Hasuike (2011) [19,33], it turns out that the LIPUS treatment undoubtedly has a beneficial effect on the process of bone healing. In the following we will show how our theoretical model can be applied to reproduce this behavior, after suitable calibration of the constitutive parameters.…”
Section: A 2d Case Simulating Growth Of Bone Tissue In the Presence Of A Bone Cavitymentioning
confidence: 98%
See 1 more Smart Citation
“…Figures 1 and 2 show the evolution of bone growth around the defect as observed during a period of approximately 1 month for the control group (not treated with ultrasound) and for the group treated with LIPUS. From the results observed by Hasuike (2011) [19,33], it turns out that the LIPUS treatment undoubtedly has a beneficial effect on the process of bone healing. In the following we will show how our theoretical model can be applied to reproduce this behavior, after suitable calibration of the constitutive parameters.…”
Section: A 2d Case Simulating Growth Of Bone Tissue In the Presence Of A Bone Cavitymentioning
confidence: 98%
“…Different authors (see [32][33][34][35]) have been interested in the experimental study of bone growth in the presence of bone defects. A common protocol is to produce a circular-shaped bone defect in the calvarium of a rat (or of another control species), thus observing in vivo, by an imaging procedure, the regeneration of bone in the weeks following surgery.…”
Section: A 2d Case Simulating Growth Of Bone Tissue In the Presence Of A Bone Cavitymentioning
confidence: 99%
“…In addition, metal membranes showed better induction of new bone than polymer membranes. In vivo, combined with LIPUS, more new bone was observed in rat calvarium defects with a cover of titanium membranes than in those with a cover of GC membrane [75]. LIPUS promoted the repair of periodontal bone defects in beagle dogs, where the bone defect was transplanted with Bio Gide ® collagen membrane + autogenous bone graft [76].…”
Section: Gbr/gtr and Xenograftmentioning
confidence: 99%
“…However, the highest mineralization was observed in the group with 2 mW/cm 2 after 17 days of LIPUS stimulation [139]. Zhou et al proposed that the LIPUS intensity of 150 mW/cm 2 from the tissue culture plate be used for further study using 3D printed scaffolds, since maximum proliferation of hBMSCs was observed at 150 mW/cm 2 among five intensities (20,50,75,150, and 300 mW/cm 2 ) [52].…”
Section: Lipus Parametersmentioning
confidence: 99%